Wearing long pants while working outdoors in the tropics does not yield higher body temperatures - Wade H. Sinclair; Jarrod C. Brownsberger (Elsevier, 2013)
Abstract Objective: To compare the thermoregulatory demands of outdoor workers wearing long or knee‐length pants while working in situ in a tropical environment. Methods: Fifteen male (35.8 ± 10.5 yr) outdoor Council workers completed their daily occupational duties (construction or gardening) in trials conducted six days apart: once wearing knee‐length shorts (SHORTS) and once wearing full‐length pants (PANTS). Body mass and hydration were assessed prior to and following each trial with core body (TC) and mean skin temperature (MST; weighted from sites: chest, arm, thigh and calf) assessed at 30‐minute intervals throughout each trial. Results: No significant differences between SHORTS and PANTS for TC, maximum TC, heart rate, MST or body mass changes. Skin temperature at the calf was greater for PANTS (33.8 ± 0.4°C) compared to SHORTS (32.9 ± 0.4°C; p<0.05). Hydration assessments identified 36.7% of participants commenced work hypohydrated while the average body mass lost throughout the workday was 2.5 ± 1.5%. Main effects of time were observed for heart rate and MST but no other assessed variable. Conclusion: The additional exposed surface area available for heat exchange when wearing shorts is insufficient to elicit differences in thermoregulatory demands of outdoor employees under the assessed conditions. Implications: These results suggest the use of SHORTS or PANTS can be determined by occupational duty requirements rather than risk of heat‐related illness during very‐light to moderate workloads completed under warm and humid environmental conditions.